Aqueous dispersion, reinforced transparent substrate, and method for producing reinforced transparent member

An aqueous dispersion of tetrafluoroethylene polymer particles with a polymer leveling agent addresses the need for improved glass container durability and transparency by forming a coating film that enhances impact resistance, heat resistance, and reduces yellowing, suitable for pharmaceutical containers.

JP2025011459APending Publication Date: 2025-01-24AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023113585
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Glass containers used for pharmaceuticals require improved impact resistance, heat resistance, transparency, and reduced yellowing to meet modern hygiene and durability standards, while existing methods struggle to form a polymer layer that adheres firmly and maintains transparency.

Method used

An aqueous dispersion containing tetrafluoroethylene polymer particles with specific properties and a polymer leveling agent is applied to form a coating film on transparent substrates, enhancing durability, heat resistance, and transparency, with low yellowing, by optimizing dispersion stability and adhesion through controlled application and firing processes.

Benefits of technology

The aqueous dispersion forms a coating film with excellent durability, heat resistance, impact resistance, and low yellowing, suitable for glass containers that can withstand high temperatures and UV exposure, maintaining transparency and improving mechanical strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an aqueous dispersion capable of forming a coating layer with superior durability, heat resistance, impact resistance, transparency and yellowing resistance.SOLUTION: An aqueous dispersion contains tetrafluoroethylene-based polymer particles with a melting temperature of 280°C-320°C and a polymer-based leveling agent with a lamellar length of 7.0 to 8.5 mm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous dispersion containing particles of a tetrafluoroethylene-based polymer, and to a reinforced transparent member formed from the aqueous dispersion. [Background technology]

[0002] Glass containers are useful as containers for storing pharmaceuticals because of their excellent chemical resistance, airtightness, transparency, etc., and are widely used as ampoules and vials. Glass is easily broken by impact, and glass containers are easily damaged by transportation and contact during filling, so a method of improving the impact resistance of glass containers by providing a polymer layer on the outer surface of the glass container has been adopted. However, it is not easy to firmly adhere the glass and the polymer layer. In recent years, glass containers are increasingly required to be sanitized. For example, glass containers used to store pharmaceuticals are often sterilized by long-term exposure to high temperatures or ultraviolet light. On the other hand, a dispersion containing tetrafluoroethylene polymer particles and a liquid dispersion medium is known as a material for forming a layer having the characteristics of a tetrafluoroethylene polymer. Patent Document 1 proposes a method for producing a reinforced glass container, in which a liquid composition containing specific tetrafluoroethylene polymer particles is applied to the outer surface of a glass container, and heated to provide a polymer layer on the outer surface of the glass container. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2022 / 149552 Summary of the Invention [Problem to be solved by the invention]

[0004] The reinforced glass container obtained by the method of Patent Document 1 has excellent impact resistance, heat resistance, and UV resistance. Meanwhile, in recent years, glass containers used to store pharmaceuticals are required to have further improved transparency and reduced yellowing depending on the application. The present inventors have found that the aqueous dispersion containing the particles of a specific tetrafluoroethylene-based polymer and a specific polymer-based leveling agent can form a coating film that is excellent in transparency and low yellowing while expressing the physical properties based on the tetrafluoroethylene-based polymer.Then, they have found that when this aqueous dispersion is used for coating a transparent substrate such as a glass substrate, a reinforced transparent substrate that is excellent in transparency and low yellowing can be produced, and can be suitably used for a glass container for storing medicines, and thus have arrived at the present invention. The object of the present invention is to provide an aqueous dispersion capable of forming a coating film having excellent durability, heat resistance, impact resistance, transparency and low yellowing. Another object of the present invention is to provide a reinforced transparent substrate coated with the aqueous dispersion, and a method for producing a reinforced transparent member. [Means for solving the problem]

[0005] The present invention has the following aspects. [1] An aqueous dispersion comprising particles of a tetrafluoroethylene-based polymer having a melting temperature of 280° C. to 320° C. and a polymer-based leveling agent having a lamellar length of 7.0 to 8.5 mm. [2] The aqueous dispersion of [1], wherein the tetrafluoroethylene-based polymer has a carbonyl group-containing group. [3] The aqueous dispersion according to [1] or [2], wherein the average particle size of the particles of the tetrafluoroethylene-based polymer is 1 μm or more. [4] The aqueous dispersion according to any one of [1] to [3], wherein the content of the tetrafluoroethylene polymer particles is 30% by mass or more. [5] The aqueous dispersion according to any one of [1] to [4], wherein the polymer-based leveling agent has a dynamic surface tension of 60 to 80 mN / m. [6] The aqueous dispersion according to any one of [1] to [5], wherein the polymer-based leveling agent has a static surface tension of 30 to 50 mN / m. [7] The aqueous dispersion according to any one of [1] to [6], wherein the polymer-based leveling agent has an HLB of 7.6 to 12. [8] The aqueous dispersion according to any one of [1] to [7], wherein the polymer-based leveling agent is an acrylic polymer or a silicone-based polymer. [9] Any of the aqueous dispersions according to [1] to [8], having a viscosity of 1000 mPa s or less.

[10] The aqueous dispersion according to any one of [1] to [9], which is used for coating a transparent substrate.

[11] The aqueous dispersion according to

[10] , wherein the transparent substrate is a glass substrate.

[12] The aqueous dispersion according to

[10] or

[11] , wherein the transparent substrate is a glass container selected from the group consisting of a vial, an ampoule, a bottle, or a cartridge.

[13] A reinforced transparent substrate coated with the aqueous dispersion of any one of

[10] to

[12] .

[14] The reinforced transparent substrate according to

[13] , wherein the reinforced transparent substrate is a glass container for containing a medicine.

[15] A method for producing a reinforced transparent substrate, comprising applying an aqueous dispersion containing particles of a tetrafluoroethylene-based polymer having a melting temperature of 280° C. to 320° C. and a polymer-based leveling agent having a lamellar length of 7.0 to 8.5 mm to an outer surface of a transparent substrate, and heating the resulting mixture to form a polymer layer containing the tetrafluoroethylene-based polymer on the outer surface of the transparent substrate. Effect of the Invention

[0006] According to the present invention, there is provided an aqueous dispersion capable of forming a coating film having excellent durability, heat resistance, impact resistance, transparency and low yellowing. The aqueous dispersion of the present invention can be suitably used for coating transparent substrates such as glass substrates, and can be used to produce glass reinforced containers such as vials, ampoules, bottles or cartridges having excellent transparency and low yellowing, which can be subjected to treatments involving exposure to high temperatures or ultraviolet light. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The following terms have the following meanings. "Average particle size (D50)" is the cumulative 50% volumetric diameter of a particle or filler determined by a laser diffraction / scattering method. In other words, the particle size distribution is measured by a laser diffraction / scattering method, the total volume of the particle or filler group is set as 100%, a cumulative curve is calculated, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of particles or fillers is determined by dispersing the particles or fillers in water and analyzing them by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). "Glass transition temperature (Tg)" is a value measured by analyzing a polymer using the dynamic mechanical analysis (DMA) method. The "viscosity" is determined by measuring the aqueous dispersion using a Brookfield viscometer at 25° C. and 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is calculated. The "thixotropy ratio" is a value calculated by dividing the viscosity of the aqueous dispersion measured at a rotation speed of 30 rpm by the viscosity of the aqueous dispersion measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values ​​is used. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."

[0008] The aqueous dispersion of the present invention (hereinafter also referred to as "the present dispersion") contains particles (hereinafter also referred to as "F particles") of a tetrafluoroethylene-based polymer (hereinafter also referred to as "F polymer") having a melting temperature of 280°C to 320°C, and a polymer-based leveling agent having a lamellar length of 7.0 to 8.5 mm. This dispersion can form a coating film based on the F polymer that is excellent in durability, heat resistance, impact resistance, and adhesion, as well as transparency and yellowing resistance.

[0009] When a polymer layer containing an F polymer is formed on the surface of a transparent substrate made of an inorganic material such as glass for the purpose of imparting durability, heat resistance, and impact resistance, it is necessary to repeatedly apply a dispersion containing F particles or to set strict conditions in the baking process in order to firmly bond the polymer layer to the transparent substrate. In this case, the transparency of the polymer layer tends to decrease or the yellowish color tends to increase, and if the transparent substrate is a three-dimensional substrate having a so-called shoulder, this tendency tends to be more pronounced at the curvature of the shoulder. In the present dispersion, the leveling agent having a specific lamellar length is presumed to improve the dispersion stability of the F particles in the present dispersion, promote the formation of dense packing of the F particles in the coating layer formed by applying the present dispersion, and relieve the stress when the coating film is obtained by baking it. As a result, it is presumed that dense melt-baking of the F polymer becomes easier, and the adhesion to the transparent substrate is improved, resulting in a coating film with excellent transparency and yellowing resistance. This effect becomes more remarkable when the present dispersion contains specific F particles described later.

[0010] In the present composition, the F polymer is a polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE") and having a melting temperature of 280°C to 320°C. The F polymer may be used alone or in combination of two or more kinds. The glass transition temperature of the F polymer is preferably 60° C. or higher, more preferably 75° C. or higher. The glass transition temperature of the F polymer is preferably 120° C. or lower, more preferably 100° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a mixture for wetting tension testing (manufactured by Wako Pure Chemical Industries, Ltd.) specified in JIS K 6768 on a flat plate made of the F polymer.

[0011] Examples of F polymers include polymers containing TFE units and units based on ethylene (ETFE), polymers containing TFE units and units based on propylene, polymers containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), and polymers containing TFE units and units based on hexafluoropropylene (FEP). F polymers are preferably PFA or FEP, and more preferably PFA. These polymers may further contain units based on other comonomers. PAVE is CF 2 =CFOCF 3 , C.F. 2 =CFOCF 2 CF 3 and CF 2 =CFOCF 2 CF 2 CF 3 (hereinafter also referred to as "PPVE") is preferred, with PPVE being more preferred.

[0012] At least one of the F polymers preferably has an oxygen-containing polar group, more preferably has a hydroxyl group-containing group or a carbonyl group-containing group, and even more preferably has a carbonyl group-containing group. In this case, when the dispersion is used for coating a transparent substrate, the coating film formed tends to have excellent durability, heat resistance, impact resistance, and adhesion. The hydroxyl group-containing group is preferably a group containing an alcoholic hydroxyl group, and -CF 2 CH 2 OH and -C(CF 3 ) 2 OH is more preferred. The carbonyl group-containing group is a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH 2), acid anhydride residue (-C(O)OC(O)-), imide residue (-C(O)NHC(O)-, etc.), formyl group, halogenoformyl group, urethane group (-NHC(O)O-), carbamoyl group (-C(O)-NH 2 ), ureido group (-NH-C(O)-NH 2 ), oxamoyl group (-NH-C(O)-C(O)-NH 2 ) and carbonate groups (-OC(O)O-), and acid anhydride residues are more preferred. When the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6 The number of oxygen-containing polar groups per unit is preferably 50 to 5000, more preferably 100 to 3000. The number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.

[0013] The oxygen-containing polar group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment.

[0014] The heat-meltable F polymer is preferably a polymer (1) that does not have an oxygen-containing polar group and contains TFE units and PAVE units, and contains 2.0 to 5.0 mol% of PAVE units based on the total units, or a polymer (2) that contains TFE units and PAVE units and has an oxygen-containing polar group. If such an F polymer is used, spherulites with a relatively small radius are easily formed. Therefore, when the dispersion is used for coating a transparent substrate, the adhesion to the transparent substrate is easily improved.

[0015] It is more preferable that the polymer (1) is composed only of TFE units and PAVE units, and contains more than 2.5 mol % and 5.0 mol % or less of PAVE units based on the total units. In addition, the fact that the polymer (1) does not have an oxygen-containing polar group means that the number of the oxygen-containing polar groups is 1×10 of the carbon atoms constituting the polymer main chain.6 This means that the number of oxygen-containing polar groups contained in the polymer is less than 50 per unit area. The lower limit of the number of oxygen-containing polar groups is 1. The polymer (1) may be produced by using a polymerization initiator or a chain transfer agent that does not generate an oxygen-containing polar group as a terminal group of the polymer chain, or by fluorinating an F polymer having an oxygen-containing polar group (such as an F polymer having an oxygen-containing polar group derived from a polymerization initiator at the terminal group of the polymer main chain). Examples of the fluorination method include a method using fluorine gas (see JP 2019-194314 A, etc.).

[0016] The polymer (2) is preferably a heat-meltable F polymer having a carbonyl group-containing group containing TFE units and PAVE units, more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in this order in an amount of 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol% relative to the total units. Specific examples of such F polymers include the polymers described in WO 2018 / 16644. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.

[0017] In this dispersion, the F polymer may be a mixture of particles of polytetrafluoroethylene (PTFE) and particles of a heat-fusible F polymer having oxygen-containing polar groups. In this case, from the viewpoints of ease of handling when using the present dispersion for coating a transparent substrate, and excellent durability, heat resistance, impact resistance, and adhesiveness of a coating film formed from the present dispersion, the content of PTFE particles in the mixture of PTFE particles and particles of a heat-fusible F polymer having an oxygen-containing polar group is preferably 50 to 90 mass%.

[0018] The F particles preferably have an average particle size (D50) of 0.1 μm or more, more preferably 1 μm or more. The D50 of the F particles is preferably 10 μm or less, more preferably 5 μm or less. In this case, the dispersion is likely to have excellent dispersibility and processability, and the dispersion is likely to have excellent handleability when used for coating a transparent substrate, and the coating film formed from the dispersion is likely to have excellent durability, heat resistance, impact resistance, and adhesion. The F particles are particles containing an F polymer, and preferably consist of an F polymer. One type of F particle may be used, or two or more types of F particles may be used. When two or more kinds of F particles are used, it is preferable that the F particles are a mixture of PTFE particles and particles of a heat-meltable F polymer having an oxygen-containing polar group. In order to obtain excellent durability, heat resistance, impact resistance, and adhesiveness of the coating film (coating film) formed from the dispersion, it is preferable that the content of PTFE particles in the mixture of PTFE particles and particles of a heat-meltable F polymer having an oxygen-containing polar group is 50 to 90 mass%.

[0019] The polymer leveling agent contained in the dispersion has a lamellar length of 7.0 to 8.5 mm, and more preferably 7.5 to 8.0 mm. Here, the lamellar length is related to the surface tension and is an index indicating how much the liquid film stretches. The lamellar length can be measured using a du Nouy surface tensiometer by the ring method according to the provisions of 6.3.2 of JIS K2241:2017. Specifically, a solution containing 50% by mass of the polymer leveling agent is used as the measurement target, and a platinum ring (ring) suspended parallel to the solution to be measured is once submerged in the solution, and then the ring is gradually pulled up in the vertical direction. At this time, a force pulling down the ring is applied by the liquid film formed between the ring and the liquid surface. After showing a maximum value (i.e., surface tension), this force gradually decreases as the amount of pulling increases, and finally becomes zero when the liquid film is destroyed. Here, the movement distance of the ring from when the force pulling down the ring shows a maximum value until the liquid film is destroyed is defined as the lamellar length. Note that "pulling up" or "pulling down" the ring refers to its movement relative to the solution being measured; for example, the ring may be fixed and the stage carrying the solution to be measured may be moved to measure the lamellar length. The solution containing 50% by mass of the polymer-based leveling agent can be prepared using a solvent in which the polymer-based leveling agent dissolves well, such as dipropylene glycol monomethyl ether.

[0020] The dynamic surface tension of the polymer-based leveling agent is preferably 60 to 80 mN / m, more preferably 63 to 77 mN / m. In this specification, the dynamic surface tension refers to the surface tension value at a frequency of 10 Hz by the maximum bubble pressure method. The dynamic surface tension can be measured, for example, using a SITA measuring device (SITA t60, Eiko Seiki Co., Ltd.). The static surface tension of the polymer-based leveling agent is preferably 30 to 50 mN / m, more preferably 33 to 47 mN / m. The static surface tension can be measured, for example, by using a surface tension measuring device (DCAT 21, manufactured by Eiko Seiki Co., Ltd.). The polymer leveling agent preferably has an HLB of 7.6 to 12. When the dynamic surface tension, static surface tension and HLB of the polymer-based leveling agent are within the above-mentioned ranges, the assumed action mechanism of the present invention described above is more effectively exerted, which is preferable from the viewpoint of easily achieving the effects of the present invention.

[0021] The polymer leveling agent contained in the present dispersion preferably has a water-insoluble polymer main chain, a water-soluble group in its side chain, and a structure showing water solubility as a whole. In other words, in addition to the above-mentioned assumed action mechanism, the polymer leveling agent contained in the present dispersion has a hydrophilic part and a hydrophobic part in the molecular structure, which adjusts the surface tension of the present dispersion and increases the wettability with the transparent substrate, thereby improving the adhesion of the coating film formed from the present dispersion. The polymeric leveling agent may be anionic, cationic, or nonionic. Examples of the polymer-based leveling agent include acrylic polymers, silicone polymers, vinyl polymers, and fluorine-based polymers. These may be used alone or in combination of two or more. Among them, the polymer-based leveling agent is preferably an acrylic polymer or a silicone polymer, and more preferably an acrylic polymer having a cationic group such as an ammonium ion, from the viewpoint of reducing the surface tension in the present dispersion, improving the wettability to a transparent substrate, and improving the adhesion of a coating film (coating film) formed from the present dispersion. In this specification, the term "acrylic polymer" refers to a (meth)acrylic polymer that contains a (meth)acrylic monomer as its main constituent unit.

[0022] Examples of the (meth)acrylic monomer include (meth)acrylic monomers having at least one of a hydroxyl group, a carboxy group, a silyl group, and an isocyanate group, and (meth)acrylic acid esters. Specifically, for example, 2-hydroxyethyl (meth)acrylate (HEMA), 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, (meth)acrylic acid, ((meth)acryloyloxy)acetic acid, 2-carboxyethyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, 1-[2-((meth)acryloyloxy)ethyl] succinate, 1-( 2-(meth)acryloyloxyethyl), 2-((meth)acryloyloxy)ethyl hydrogen hexahydrophthalate, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, phenyl (meth)acrylate Acrylate, benzyl (meth)acrylate, glycidyl (meth)acrylate, allyl glycidyl ether, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, aminoethyl (meth)acrylate, N-monoalkylaminoalkyl (meth)acrylate, N,N-dialkylaminoalkyl (meth)acrylate, 2-aziridinylethyl (meth)acrylate, dicyclopentaerythritol, Thenyl (meth)acrylate, allyl (meth)acrylate, acetoacetoxyethyl (meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, allyl (meth)acrylate, and γ-(meth)acryloxypropyltrimethoxysilane. In this specification, "(meth)acrylic" is a term that collectively refers to acrylic, methacrylic, and both, and "(meth)acrylate" is a term that collectively refers to acrylate, methacrylate, and both. The acrylic polymer may be a copolymer with other polymerizable monomers in addition to the above-mentioned (meth)acrylic monomers. Examples of the other polymerizable monomers include vinyl esters, vinyl ethers, vinyl aromatic compounds, (meth)acrylonitrile, and polymerizable monomers containing a methylolamide group, a silyl group, an oxazoline group, an amide group, and a carbonyl group. In the case of a copolymer with other polymerizable monomers, the proportion of the structural unit derived from the other polymerizable monomer in the acrylic polymer is preferably 10 to 90 mol%.

[0023] Examples of the silicone polymer include modified silicone polymers such as polydimethylsiloxane, polyether modified polydimethylsiloxane, acrylic modified polydimethylsiloxane, and polyester modified polydimethylsiloxane.

[0024] Specific examples of polymer-based leveling agents include poly(2-hydroxy-3-methacryloyloxypropyltrimethylammonium chloride), poly(dimethylaminoethyl methacrylate), poly(methacryloyloxypropylsulfonic acid); copolymers of alkylaminoalkyl(meth)acrylamides and alkyl(meth)acrylate acrylamides or acrylonitrile; salts of acrylic acid polymers with alkali metals, amines, and ammonia; copolymers of maleic anhydride and acrylic acid, copolymers of itaconic acid and acrylic acid, and salts of these with alkali metals, amines, and ammonia.

[0025] The content of the polymer-based leveling agent is preferably 0.1 to 1 mass % relative to the content of the F particles in the present dispersion. Within this range, the fluidity and dispersion stability of the present dispersion can be improved, and the transparency and yellowing resistance of the coating film formed from the present dispersion can be improved.

[0026] As the polymer-based leveling agent, commercially available products may be used, such as the BYK series manufactured by BYK Japan, the Tego series manufactured by EVONIK, the Granol series and Polyflow series manufactured by Kyoeisha Chemical Co., Ltd., and the Disparlon series manufactured by Kusumoto Chemical Industries, Ltd. Specific examples include BYK-381 (an ionic solution of an acrylic leveling additive which is a polyacrylic acid copolymer; lamellar length 7.55 mm, dynamic surface tension 71.3 mN / m, static surface tension 38.8 mN / m), BYK-346 (lamellar length 7.40 mm, dynamic surface tension 51.5 mN / m, static surface tension 21.6 mN / m), and BYK-347 (a silicone-based polymer; lamellar length 7.46 mm, dynamic surface tension 68.7 mN / m, static surface tension 21.9 mN / m), all of which are manufactured by BYK Japan.

[0027] The present dispersion may further contain another resin different from the F polymer, as long as the effect of the present invention is not impaired. Such another resin may be contained in the present dispersion as non-hollow particles, or may be dissolved or dispersed in the present dispersion. Examples of other resins include polyester resins such as liquid crystalline aromatic polyesters, polyimide resins, polyamideimide resins, epoxy resins, maleimide resins, urethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. When the present dispersion liquid further contains another resin, the content thereof relative to the F particles is preferably 1 to 25% by mass.

[0028] The dispersion may further contain an inorganic filler within a range that does not impair the effects of the present invention. The inorganic filler may have various shapes such as spherical, needle-like, fibrous, plate-like, scaly, and layer-like shapes. Examples of inorganic fillers include silicon compounds such as quartz powder, silica, wollastonite, talc, silicon nitride, silicon carbide, and mica; nitrogen compounds such as boron nitride and aluminum nitride; metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide; carbon fibers; carbon allotropes such as graphite, graphene, and carbon nanotubes; and metals such as silver and copper. The inorganic filler preferably has a D50 of 0.1 to 50 μm. The surface of the inorganic filler may be treated with a silane coupling agent. The inorganic filler may be used alone or in combination of two or more kinds.

[0029] The dispersion may further contain a solvent within a range that does not impair the effects of the present invention. The solvent is preferably a compound that is liquid at 25°C under atmospheric pressure, has a boiling point of 50 to 240°C, and is miscible with water. The solvent is preferably at least one selected from the group consisting of amides, ketones, and esters. One type of solvent may be used, or two or more types may be used. Examples of amides include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone. Examples of the ketone include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone. Examples of the ester include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, γ-butyrolactone, and γ-valerolactone.

[0030] The present dispersion may further contain a pH adjuster such as an amine, ammonia, or citric acid, or a pH buffer such as tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium bicarbonate, ammonium carbonate, or ammonium acetate, within a range that does not impair the effects of the present invention.

[0031] The dispersion may further contain a surfactant different from the above-mentioned polymer-based leveling agent. The surfactant is preferably a nonionic surfactant. Examples of the nonionic surfactant include glycol-based surfactants, acetylene-based surfactants, silicone-based surfactants, and fluorine-based surfactants.

[0032] The present dispersion may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, and a flame retardant.

[0033] The content of F particles in the present dispersion is preferably 25% by mass or more, more preferably 30% by mass or more, and is preferably 75% by mass or less, more preferably 60% by mass or less. The viscosity of the dispersion is preferably 1000 mPa·s or less, more preferably 500 mPa·s or less. The viscosity of the dispersion is preferably 10 mPa·s or more, more preferably 20 mPa·s or more. In this case, the dispersion is easy to handle when used for coating a transparent substrate, and the physical properties of the F polymer are easily expressed in the coating film formed therefrom. The thixotropy ratio of the present dispersion is preferably 1.0 to 3.0.

[0034] The solid content of the present dispersion is preferably 20% by volume or more, more preferably 40% by volume or more. The solid content is preferably 80% by volume or less, more preferably 70% by volume or less. The solid content means the total amount of substances that form solid content in the coating film formed from the present dispersion. Specifically, F particles and polymer-based leveling agents are solid content, and when the present dispersion contains other resins or inorganic fillers, the other resins and inorganic fillers are also solid content, and the total volume concentration of these components is the solid content concentration of the present dispersion.

[0035] This dispersion is obtained by mixing F particles, the above-mentioned polymer-based leveling agent, water, and, if necessary, other resins, other inorganic fillers, surfactants, additives, etc. There is no particular restriction on the order of mixing, and the mixing method may be either mixing all at once or mixing in multiple batches. Mixing devices for obtaining the present dispersion include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.

[0036] The present dispersion can be suitably used for coating a transparent substrate, in other words, the present dispersion is also a coating agent for a transparent substrate. The transparent substrate is preferably a glass substrate, more preferably a glass container. In particular, it can be suitably used as a container for storing and storing pharmaceuticals. Examples of such containers include vials, ampoules, bottles, cartridges, syringes (outer cylinders and plungers), beakers, petri dishes, etc., and it is more preferable for the transparent substrate to be a glass container selected from the group consisting of vials, ampoules, bottles, and cartridges. Glass containers intended for pharmaceutical use are preferably formed from glasses that meet the standards for pharmaceutical glasses set forth by regulatory agencies such as the United States Pharmacopoeia, the European Pharmacopoeia, and the Japanese Pharmacopoeia, based on their resistance to hydrolysis.

[0037] As the glass, soda-lime glass, alkali aluminosilicate glass, or borosilicate glass is preferable, and alkali aluminosilicate glass or borosilicate glass is more preferable. These glasses are preferable because they have a low linear expansion coefficient, are resistant to thermal shock, and are excellent in chemical resistance. In addition, the glass has a diameter of 25×10 -7 ~80×10 -7 It is preferable that the material has a linear thermal expansion coefficient of 100 / °C. Alkali aluminosilicate glasses are generally made up of Na 2 O and / or K 2 O and SiO 2 and Al 2 O 3 and optionally at least one alkaline earth metal oxide and at least one alkali metal oxide. The alkali aluminosilicate glass is preferably free of boron and boron-containing compounds. Alkali aluminosilicate glass is SnO 2 , ZrO 2 , ZnO, TiO 2 and As 2 O 3 The composition may contain a small amount of at least one oxide selected from the group consisting of: These components are added as a clarifying agent and / or a chemical durability improving agent. Specific examples of borosilicate glasses include Corning® Pyrex® 7740, 7800 and Wheaton 180, 200, 400, Schott Duran, Schott Fiolax, KIMAX® N-51A, Gerrescheimer GX-51 Flint, and the like. Specific examples of soda lime glass include Wheaton 800 and 900. As the soda lime glass, ammonium sulfate-treated soda lime glass may be used.

[0038] The glass container may be strengthened by a method such as ion exchange strengthening, heat strengthening, or flame polishing prior to the formation of the F layer to improve mechanical durability. For example, the glass container may be strengthened by ion exchange strengthening by immersing the glass container in 100% KNO 3 One example is where the glass is immersed in a molten salt bath at 450° C. for about 8 hours; in this case, the glass is also called "ion-exchanged glass." The glass container may also be formed from a glass composition containing ion-exchangeable and non-ion-exchangeable glasses, and may be formed from a Type 1B glass composition such as Schott Type 1B aluminosilicate glass. In addition, the outer surface of the glass container is coated with SnO 2 , ZrO 2 , ZnO, TiO 2 , As 2 O 3 A coating containing the above may be formed. The compressive stress of the glass container is preferably 300 MPa or more, more preferably 350 MPa or more, and is preferably 900 MPa or less. The thickness (wall thickness) of the glass container is preferably 50 μm or more, more preferably 100 μm or more, and is preferably 2 mm or less, more preferably 1 mm or less.

[0039] The present invention includes a method for producing a reinforced transparent substrate (hereinafter also referred to as "the method"), which comprises applying the present dispersion to the outer surface of a transparent substrate and heating the substrate to form a polymer layer (hereinafter also referred to as "F layer") containing an F polymer on the outer surface of the transparent substrate. Since such a reinforced transparent substrate has an F layer, it is excellent in durability, heat resistance, impact resistance, transparency and low yellowing even when the reinforced transparent substrate is a glass container for storing medicines, which has a relatively small thickness.

[0040] In this method, it is preferred to directly apply the present dispersion to the outer surface of the transparent substrate. In other words, in this method, it is preferred to apply the present dispersion to the outer surface of the transparent substrate, and heat it to directly form an F layer on the outer surface of the transparent substrate. In this case, for the reasons mentioned above, the durability, heat resistance, impact resistance, transparency and low yellowing of the obtained reinforced transparent substrate are more likely to be improved.

[0041] The transparent substrate is preferably the above-mentioned glass substrate, and a glass container selected from the group consisting of a vial, an ampoule, a bottle, or a cartridge can be suitably used. Methods for applying the present dispersion to the outer surface of a transparent substrate include dip coating, spraying (spraying using a spray gun), roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar method, slot die coating, etc. Among these, the dip coating method is preferred from the viewpoint of more easily forming an F layer on the outer surface of a transparent substrate.

[0042] The dispersion applied to the outer surface of the transparent substrate is heated to remove water and other solvents that may be contained therein (drying) by preliminary heating to obtain a dry coating. When removing water and other solvents that may be contained therein, air or an inert gas such as nitrogen may be used for air drying. Next, the transparent substrate having the dried coating is heated to bake the F polymer. Heating is preferably performed in a temperature range equal to or higher than the melting temperature of the F polymer, specifically, at 340 to 400° C. for 0.1 to 30 minutes. The heating device may be an oven or a ventilation drying furnace. The heat source in the heating device may be a contact type heat source such as hot air or a hot plate, or a non-contact type heat source such as infrared rays. The heating may be performed under atmospheric pressure or under reduced pressure, and the heating atmosphere may be either an air atmosphere or an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.). In this manner, the F layer is formed on the outer surface of the transparent substrate.

[0043] The F layer may be formed by carrying out the steps of applying and drying the present dispersion to the outer surface of the transparent substrate only once, or may be formed by carrying out the steps two or more times. For example, the present dispersion may be applied to the outer surface of the transparent substrate and dried to obtain a dry coating, the present dispersion may be further applied to this dry coating and dried to obtain a thick dry coating, and then the dry coating (F polymer) may be baked by heating to form the F layer.

[0044] The present invention also includes reinforced transparent substrates coated with the present dispersions, such reinforced transparent substrates being suitable for production, for example, by the present method. The reinforced transparent substrate is preferably a glass container for containing medicines. Such a glass container is exposed to an atmosphere having a temperature of 200°C or higher and lower than the melting temperature of the F polymer, for example, at 250 to 300°C for 0.5 to 12 hours, or exposed to ultraviolet light of 240 to 290 nm with an integrated dose of 1 to 200 mJ / cm. 2 A sterilized glass container is obtained by exposing the container to a range of 100° C., and then the container is filled with a medicine and sealed to obtain a medicine container in which the medicine is contained in the container. The pharmaceuticals contained therein include chemical substances themselves that can be used for the diagnosis, treatment, cure, or prevention of diseases, compositions containing at least one such chemical substance, etc. The pharmaceuticals may be in any form, such as liquid, solid, gel, suspension, emulsion, powder, etc.

[0045] Although the present dispersion, the reinforced transparent substrate, and the method for producing the reinforced transparent substrate have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the present dispersion, the reinforced transparent substrate, and the method for producing the reinforced transparent substrate may have any other configuration in addition to the configurations of the above-mentioned embodiments, or may be replaced with any configuration that produces a similar effect. EXAMPLES

[0046] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [F Polymer] F particle 1: containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of TFE units, NAH units, and PPVE units, in that order, and having a carbonyl group-containing group with a main chain carbon number of 1×10 6 Tetrafluoroethylene polymer particles (melting temperature: 300°C) with 1000 particles per particle (D50: 2.1 μm) [Polymer-based leveling agent] Agent 1: BYK-381 (BYK, polymer leveling agent made of acrylic polymer, lamellar length 7.55 mm, dynamic surface tension 71.3 mN / m, static surface tension 38.8 mN / m) The lamellar length is a value measured by the above-mentioned method using a dipropylene glycol monomethyl ether solution containing 50% by mass of a polymer-based leveling agent. [Glass container] Glass container 1: Vial made of borosilicate glass (thickness: 2 mm)

[0047] 2. Example of production of aqueous dispersion [Example 1] F particles 1, agent 1, and water were added to the pot, and zirconia balls were then added. The pot was then rolled at 150 rpm for 1 hour to produce aqueous dispersion 1 (viscosity: 30 mPa s, pH: 8 to 9) containing F particles 1 (40 parts by mass), agent 1 (2 parts by mass), and water (58 parts by mass). [Example 2] The same procedure as in Example 1 was carried out except that Agent 1 was not added, to produce an aqueous dispersion 2 (viscosity: 20 mPa·s, pH: 9) containing F particles 1 (40 parts by mass) and water (60 parts by mass).

[0048] 3. Manufacturing examples of reinforced glass containers [Example 3] A liquid coating was formed on the outer surface of the glass container 1 by a dip coating method in which the glass container 1 was immersed in the aqueous dispersion liquid 1. Next, the glass container 1 on which the liquid coating was formed was passed through a drying oven at 120°C for 5 minutes and dried by heating to obtain a dry coating. The dry coating was then heated at 380°C for 3 minutes in a nitrogen oven. This resulted in a reinforced glass container 1 having the glass container 1 and an F layer (thickness: 25 μm) containing a molten-sintered product of the F particles 1 on its outer surface. [Example 4] A reinforced glass container 2 was obtained in the same manner as in Example 3, except that Aqueous Dispersion 2 was used instead of Aqueous Dispersion 1.

[0049] A rectangular cut was made in the F layer of glass reinforced containers 1 and 2, and the rectangular piece was peeled off at 90° from one end of the length direction at a tensile speed of 50 mm / min using a tensile tester. The maximum load measured was recorded as the peel strength (N / cm). The peel strength of all of the glass reinforced containers was 8 N / cm or more. Further, the reinforced glass containers 1 and 2 were heated in an oven at 260° C. for 1 hour. After heating, the light transmittance of the side surface of the reinforced glass container 1 at wavelengths of 255 to 355 nm was 90% or more, and the yellowing degree of the shoulder portion at the upper end of the reinforced glass container 1 was significantly reduced compared to that of the reinforced glass container 2. [Industrial Applicability]

[0050] The aqueous dispersion of the present invention can form a coating film having excellent durability, heat resistance, impact resistance, transparency, and low yellowing. Therefore, the aqueous dispersion of the present invention is useful for coating transparent substrates such as glass substrates, and can produce reinforced glass containers such as vials, ampoules, bottles, and cartridges that have impact resistance, can be subjected to treatment involving exposure to high temperatures and ultraviolet light, and have excellent transparency and low yellowing.

Claims

1. An aqueous dispersion comprising particles of a tetrafluoroethylene-based polymer having a melting temperature of 280° C. to 320° C. and a polymer-based leveling agent having a lamellar length of 7.0 to 8.5 mm.

2. The aqueous dispersion according to claim 1 , wherein the tetrafluoroethylene-based polymer has a carbonyl group-containing group.

3. 2. The aqueous dispersion according to claim 1, wherein the average particle size of the tetrafluoroethylene-based polymer particles is 1 μm or more.

4. The aqueous dispersion according to claim 1 , wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more.

5. 2. The aqueous dispersion of claim 1, wherein the polymeric leveling agent has a dynamic surface tension of 60 to 80 mN / m.

6. 2. The aqueous dispersion of claim 1, wherein the polymeric leveling agent has a static surface tension of 30 to 50 mN / m.

7. 2. The aqueous dispersion of claim 1, wherein the polymeric leveling agent has an HLB of 7.6 to 12.

8. The aqueous dispersion of claim 1 , wherein the polymeric leveling agent is an acrylic-based polymer or a silicone-based polymer.

9. 2. The aqueous dispersion according to claim 1, having a viscosity of 1000 mPa·s or less.

10. 10. The aqueous dispersion of claim 1 for use in coating a transparent substrate.

11. The aqueous dispersion of claim 10, wherein the transparent substrate is a glass substrate.

12. 11. The aqueous dispersion of claim 10, wherein the transparent substrate is a glass container selected from the group consisting of a vial, an ampoule, a bottle, or a cartridge.

13. A reinforced transparent substrate coated with the aqueous dispersion of any one of claims 10 to 12.

14. 14. The reinforced transparent substrate of claim 13, wherein the reinforced transparent substrate is a glass container for containing a pharmaceutical product.

15. A method for producing a reinforced transparent substrate, comprising: applying an aqueous dispersion containing particles of a tetrafluoroethylene-based polymer having a melting temperature of 280° C. to 320° C. and a polymer-based leveling agent having a lamellar length of 7.0 to 8.5 mm to an outer surface of a transparent substrate; and heating the aqueous dispersion to form a polymer layer containing the tetrafluoroethylene-based polymer on the outer surface of the transparent substrate.

Citation Information

Patent Citations

  • Reinforced glass vessel, method for producing medical drug container, and method for producing reinforced glass vessel

    WO2022149552A1